DIMENSI SOSIAL DAN SPIRITUAL IBADAH ZAKAT - Karim, Abdul (ZISWAF, 2015)
Surely  Allah  commands  Zakat  is  not  just  carried  out  according  to  the  size and content of its provisions to the people who deserve (mustahiq), but more than just obligations to be implemented. Zakat is not only a divine dimension (hablum minallah) but also has a social dimension of humanity (hablum minannas). Therefore charity is a necessity indeed a servant of God who gifted fortune  to  share  with  his  fellow  creatures.  Commandments  of  zakat  in  the  Qur’an has a very profound message of social sensitivity of humanity as well as foster the spiritual values that can shape the character of humanity filled with  concern  for  the  environment.  With  a  Muslim  charity  will  be  met  in  a  tangle of Islamic brotherhood is a close, and with zakat, a man believed to have a more worldly perspective ascetic (ascetic) that makes a person no longer has the heart to the world’s dependence excessive, so be a better person thanks and happy in various situations and conditions